Risk factors for hepatocellular carcinoma in Caucasian patients with non‐viral cirrhosis: the importance of prior obesity. (21st January 2015) - Archambeaud, Isabelle; Auble, Hélène; Nahon, Pierre; Planche, Lucie; Fallot, Guillaume; Faroux, Roger; Gournay, Jérôme; Samuel, Didier; Kury, Sebastien; Féray, Cyrille
Abstract Background & Aims In patients with cirrhosis, the risk of hepatocellular carcinoma (HCC) depends upon age, gender and the etiology of liver disease. Few studies are available in Caucasian patients with alcoholic or metabolic cirrhosis without viral hepatitis. Methods Cross‐sectional clinical data from 905 HCV‐ and HBV‐negative Caucasian patients with alcoholic or metabolic cirrhosis were prospectively collected in four French centres. The risk factors for HCC were identified by logistic regression analysis in the whole population and in a nested case–control study. Results The etiology of cirrhosis was alcoholic (48%), metabolic (7%) or mixed (45%). Patients were predominantly male (80%), mean age 62 years old and 31% had HCC. Mean body mass index (BMI) was 27 ± 5 and 30% were obese at inclusion. The maximum BMI reached throughout life was 31 ± 6 and 63% had been obese. Ninety percent of the population had daily alcohol consumption, 73% were smokers. Hepatocellular carcinoma was independently related to male gender (P < 0.0001), older age (P < 0.0001), past obesity (P = 0.007), diabetes (P = 0.037), abnormal levels of transaminases (P < 0.0001) and tobacco consumption (P = 0.007). The case–control study (200 HCC cases matched with 400 non‐HCC cases for gender, age and Child‐Pugh score) confirmed past obesity, tobacco and abnormal levels of transaminases. Conclusions Beside diabetes, male gender and age, a past history of obesity, but not an existing overweight, as well as exposure to tobacco and elevated transaminases were three risk factors which could improve the strategy for HCC screening in Caucasian cirrhotic patients without hepatitis B or C.